Formulasi Perlindungan Hukum terhadap Korban Tindak Pidana Penguntitan Perspektif HAM - Lisnawati; Zainal Arifin; Huzaimah Al-Ansori; Maria Febriana; Rinni Puspitasar (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Law is an important part of upholding justice for the protection of society thus the implementation of the law must provide benefits and usefulness to society so that the implementation of the law does not cause unrest and doubt in society. In this research, the author uses a type of legal research or what is more familiar in Indonesia, namely Normative Research through journal sources from various researchers. The research results show that legal protection for victims of stalking is substantial since stalking is a form of violence that can harm victims physically, mentally, and socially. Physically, stalking can cause injury and even death to its victims. Psychologically, stalking can cause anxiety, fear, stress, and depression in the victim. Furthermore, socially, stalking can isolate victims from their environment and cause them to lose self-confidence. In the Criminal Code and the Law, some articles can be linked to Stalking because they contain several elements of Stalking behaviour implicitly as in article 493 of the Criminal Code and article 317 of Law Number 1 of 2023. Considering the criminal aspects of the act explained previously, the act of stalking can be considered to fulfil the elements of a criminal act because stalking fulfils the aspects of human action.